Sodium intake and the risk of various types of cardiovascular diseases: a Mendelian randomization study - Fu, Qingming; Chen, Rumeng; Ding, Yining; Xu, Shuling; Huang, Chunxia; He, Binsheng; Jiang, Ting; Zeng, Bin; Bao, Meihua; Li, Sen (Frontiers in Nutrition, 2023)
Background: The existing literature on the link between sodium intake and cardiovascular disease (CVD) largely consists of observational studies that have yielded inconsistent conclusions. In this study, our objective is to assess the causal relationship between sodium intake and 50 CVDs using a two-way Mendelian randomization (MR) analysis. Methods: MR analyses were performed to investigate the associations between urinary sodium/creatinine ratio (UNa/UCr), an indicator of sodium intake, and 50 CVDs. The genome-wide association study (GWAS) for UNa/UCr was from the UK Biobank (UKBB), and the GWASs for CVDs were from the FinnGen. A false discovery rate (FDR) threshold of 5% was applied for multiple comparison correction. Results: The inverse-variance weighted method indicated that the genetically predicted UNa/UCr was significantly associated with 7 of 50 CVDs, including "Coronary atherosclerosis" (OR=2.01; 95% CI: 1.37, 2.95), "Diseases of arteries, arterioles and capillaries" (OR=1.88; 95% CI: 1.20, 2.94), "Hard cardiovascular diseases" (OR=1.71; 95% CI: 1.24, 2.35), "Ischemic heart diseases" (OR=2.06; 95% CI: 1.46, 2.93), "Major coronary heart disease event" (OR=1.99; 95% CI: 1.36, 2.91), "Myocardial infarction" (OR=2.03; 95% CI: 1.29, 3.19), and "Peripheral artery disease" (OR=2.50; 95% CI: 1.35, 4.63). Similar results were obtained with the MR-Egger and weighted median methods. No significant heterogeneity or horizontal pleiotropy was found in this analysis. Conclusion：Our study has uncovered a significant positive causal relationship between UNa/UCr and various CVDs. These results offer a new theoretical foundation for advocating the restriction of sodium intake as a preventive measure against CVD.